How external management consultants add value in IS strategy in the public sector - Cussen, Edmond J. (Trinity College (Dublin, Ireland). Trinity Business School, 2009)
Information systems (IS) can transform an organisation and there are now many business models which are fiindamentally defined by technology. Despite the success stories, IS initiatives have been prone to failures which are exemplified by public sector experience in the USA where losses due to IS failures have exceeded $50 billion in a single year. Private and public sector organisations have typically made IS investment and resourcing decisions on the basis of IS strategies which have, understandably, been an area of focus for academic IS researchers over several decades. Research in the IS field has shown that failures in IS strategy are rarely attributable to technology. Failure is much more likely to stem from people or process issues. Against this background, it is striking that academic research in IS strategy formation has focused to a far greater extent on the methodologies and tools used in IS strategy formation and has paid far less attention to the participants in the process and their roles.
Keywords: Business, Ph.D.; Ph.D. Trinity College Dublin